Fish farming An ocean of opportunity for enhanced income and livelihood - Singh, S K; Dubey, S K; Yadav, Seema; Singh, Raghwendra (Indian Farming, 2024)
Fish farming plays a vital role in improving the socio-economic conditions and livelihood of rural communities. Many studies have shown that pond fish farming is more profitable enterprise than rice cultivation, promoting many poor farmers in rural areas to switch to fish farming with the benefit cost ratio ranging from 1.7 to 1.9. Furthermore, the increasing human population has created a lot of pressure on diminishing agricultural land for food production. Fish farming can be considered as an alternative source of livelihood generation and may act as bridge for achieving one of the goals of SDGs (sustainable development goals) i.e. zero hunger. The blue revolution has significant role in post independence increased production of fish which is considered as a cheap source of protein and contains essential amino acids and fatty acids. The Krishi Vigyan Kendras have emerged as connecting link between the poor farmers and new technology which led to the enhanced production of fish besides livelihood generation.